Propuesta de un medio filtrante biodegradable mediante fibras de celulosa a partir del bagazo de caña azúcar. (2022)
A proposal is developed for a filter media using cellulose fibers from sugarcane residues, to be incorporated in cloth masks and contribute to filtering efficiency, being sugarcane the second most widespread crop in Colombia. Based on the contamination caused by surgical masks and the uncertainty associated with the filtration of cloth masks, residual lignocellulosic compounds used in non-medical fields are used.